Evaluation of whole toasted and extruded soybean on the performance of broilers - Sakomura, N. K.; da Silva, R.; Laurentz, A. C.; Malheiros, E. B.; Nakaji, LSO (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
This experiment was conducted to compare the performance of 1260 chicks fed diets containing soybean meal plus soybean oil (SBM + oil), whole extruded soybean (ESB) and whole steam toasted soybean (TSB), with two protein levels. A complete randomized design was used, with six treatments and 3 replicates of each sex. The treatments consisted of a factorial arrangement 2 x 3 x 2 to test three soybean types (SBM + oil, ESB and TSB), two protein levels (optimum and suboptimum) and two sexes. From 1 to 49 days of age, the tested soybean types did not affect the diet intake. However, ESB provided higher weight gain in relation to SBM + oil, but it did not differ from TSB. The feed:gain ratio obtained with ESB and TSB was better in relation to SBM + oil. There was no difference between the nutritional value of TSB and ESB, because they provided similar performance to the birds.
Keywords: broilers; whole-extruded soybean; whole toasted soybean